A computational framework for fast‐time hybrid simulation based on partitioned time integration and state‐space modeling. Issue 10 (17th July 2019) - Abbiati, Giuseppe; Lanese, Igor; Cazzador, Enrico; Bursi, Oreste S.; Pavese, Alberto
Summary: Hybrid simulation reproduces the experimental response of large‐ or even full‐scale structures subjected to a realistic excitation with reduced costs compared with shake table testing. A real‐time control system emulates the interaction between numerical substructures, which replace subparts having well‐established computational models, and physical substructures tested in the laboratory. In this context, state‐space modeling, which is quite popular in the community of automatic control, offers a computationally cheaper alternative to the finite‐element method for implementing nonlinear numerical substructures for fast‐time hybrid simulation, that is, with testing timescale close to one. This standpoint motivated the development of a computational framework based on partitioned time integration, which is well suited for hard real‐time implementations. Partitioned time integration, which relies on a dual assembly of substructures, enables coupling of state‐space equations discretized with heterogeneous time step sizes. In order to avoid actuators stopping at each simulation step, the physical substructure response is integrated with the same rate of control system, whereas a larger time step size is allowed on the numerical substructure compatibly with available computational resources. Fast‐time hybrid simulations of a two‐pier reinforced concrete bridge tested at the EUCENTRE Experimental Laboratory of Pavia, Italy, are presented as verification example.